Microbiological aspects of osteomyelitis in veterinary medicine: drawing parallels to the infection in human medicine. Issue 1 (31st December 2022) - González-Martín, Margarita; Silva, Vanessa; Poeta, Patricia; Corbera, Juan Alberto; Tejedor-Junco, María Teresa
Abstract: Osteomyelitis is a challenging infectious disease affecting humans and animals. It is difficult to diagnose because, in many cases, symptoms are non-specific and, for example in implant-related cases, can appear long time after surgery. In addition to this, it is also difficult to treat due to the need to find the appropriate antibiotic regime and delivery system to reach the site of infection and to avoid development of bacterial resistance. The central purpose of this review is to compare the microbiological aspects of osteomyelitis in human and veterinary medicine, with the aim of improving the microbiological diagnosis and treatment of this infection in animals. Furthermore, the study of osteomyelitis in animals may help to improve the development of animal models for testing new treatments in humans. Host factors and underlying conditions have been studied mainly in humans, although aspects as immunodeficiency have been described in some veterinary cases. Even when Staphylococcus aureus is still considered the most prevalent causing microorganism, this prevalence should be reviewed using molecular diagnostic techniques, and this could affect treatment options. New approaches to treatment include local delivery of antibiotics using different biomaterials, antimicrobial photodynamic therapy, and new antimicrobial compounds. We would like to remark the need of large, high-quality clinical trials and of the development of guides for the diagnosis and treatment of osteomyelitis in different animal species.